Simulasi Hybrid MP-QUIC dalam Internet-of-Things Pertanian Pintar - Muhammad Hafidh Firmansyah; Dewanto, Wahyu Kurnia (Elkom : Jurnal Elektronika dan Komputer, 2024)
At this moment, IoT technology was implemented in a broader area. The development of IoT technology can help human life become more manageable. IoT systems can help human activity through the natural time control system provided before. But there are some drawbacks when implementing the IoT system. One of them is the transmission process in the networking area. It’s happened because of weather, and other natural problems. Sometimes, IoT transmission can’t reach on time. It can make errors reading data on the user side. We proposed a transmission system, namely a Hybrid MP-QUIC transmission protocol, for helping in sending the data. Using this transmission protocol can reduce the response time between client and server.